Association between CFH, CFB, ARMS2, SERPINF1, VEGFR1 and VEGF polymorphisms and anatomical and functional response to ranibizumab treatment in neovascular age‐related macular degeneration. Issue 2 (19th September 2017) - Cobos, Estefania; Recalde, Sergio; Anter, Jaouad; Hernandez‐Sanchez, Maria; Barreales, Carla; Olavarrieta, Leticia; Valverde, Alicia; Suarez‐Figueroa, Marta; Cruz, Fernando; Abraldes, Maximino; Pérez‐Pérez, Julian; Fernández‐Robredo, Patricia; et al.
Abstract: Purpose: We sought to determine if specific genetic single nucleotide polymorphisms (SNPs) influence vascular endothelial growth factor inhibition response to ranibizumab in neovascular age‐related macular degeneration (AMD). Methods: A total of 403 Caucasian patients diagnosed with exudative AMD were included. After a three‐injection loading phase, a pro re nata regimen was followed. Nine SNPs from six different genes ( CFH, CFB, ARMS2, SERPINF1, VEGFR1, VEGF ) were genotyped. Non‐genetic risk factors (gender, smoking habit and hypertension) were also assessed. Patients were classified as good or poor responders (GR or PR) according to functional (visual acuity), anatomical (foveal thickness measured by OCT) and fluid criteria (fluid/no fluid measured by OCT). Results: Hypertension was the environmental factor with the strongest poor response association with ranibizumab in the anatomical measure after the loading phase (p = 0.0004; OR 3.7; 95% CI, 2.4–5.8) and after 12 months of treatment (p = 10 −5 ; OR 2.3; 95% CI, 1.5–3.4). The genetic variants rs12614 ( CFB ), rs699947 ( VEGFA ) and rs7993418 ( VEGFR1 ) predisposed patients to a good response, while rs12603486 and rs1136287 ( SERPINF1 ) were associated with a poor response. The protective genotype of rs800292 variant ( CFH ) was also associated with a poor anatomical response (p 0.0048). Conclusion: All these data suggest that genetics play an important role in treatment response in AMD patients.